PERFORMANCE BASED NAVIGATION AND AIRSPACE CONCEPT - Kharchenko, Volodymyr P.; Luppo, Alexander E.; Lazorenko, Vitaliy A. (Proceedings of National Aviation University (archive), 2009)
Performance based navigation integration and Airspace Concept are described. Connectivity of performance based navigation and airspace concept is considered. Analysis of effectiveness of relationship between performance based navigation and airspace concept is given.